2020
DOI: 10.3389/fphys.2020.575060
|View full text |Cite
|
Sign up to set email alerts
|

Rest-Phase Hypothermia Reveals a Link Between Aging and Oxidative Stress: A Novel Hypothesis

Abstract: In endotherms, growth, reproduction, and survival are highly depended on energy metabolism. Maintenance of constant body temperature can be challenging for endotherms under continuously changing environmental conditions, such as low or high ambient temperatures or limited food. Thus, many birds may drop body temperature below normothermic values during the night, known as rest-phase hypothermia, presumably to decrease energy metabolism. Under the assumption of the positive link between aerobic metabolism and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Hypothermia is characterised by widespread metabolism reduction that affects all bodily systems at the same time. Between 50 and 90 percent of surgery patients suffer from hypothermia at some point throughout their recovery period [ 4 , 5 ]. The consequence is significant physiological alterations, including changed heart function, fluctuations in state of awareness, shivering and extended plasma half-lives of medicines, which may also enhance oxygen consumption by up to 500 percent [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypothermia is characterised by widespread metabolism reduction that affects all bodily systems at the same time. Between 50 and 90 percent of surgery patients suffer from hypothermia at some point throughout their recovery period [ 4 , 5 ]. The consequence is significant physiological alterations, including changed heart function, fluctuations in state of awareness, shivering and extended plasma half-lives of medicines, which may also enhance oxygen consumption by up to 500 percent [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible, therefore, that rest-phase hypothermia may come at the cost of increased oxidative stress (cf. 57 ). It is interesting to note that this acute response to reduced air temperature is opposite to what has been recorded as part of seasonal acclimatisation in the same model system 20 and in response to cold exposure in tissues with more clearly defined metabolic or thermogenic roles in other models (see references above).…”
Section: Discussionmentioning
confidence: 99%
“…it is possible that rest-phase hypothermia may come at the cost of increased oxidative stress [cf. 57]. Future work should explore this hypothesis by direct measurement of ATP- and ROS production, and membrane potential, to conclude on the consequences of changes to the efficiency of phosphorylating respiration for redox balance in normo- and hypothermic birds.…”
Section: Discussionmentioning
confidence: 99%
“…Thermoregulatory function declines with aging 29 , and one of the causes is an aging-associated decrease in production of NO, which has a vasodilator effect 30 . Some researchers reported that poorer thermoregulation with aging is related to suppression of mitochondria metabolism, increased ROS production, and accumulated oxidative damage to cells 31 . Thus, because aging is related to cold intolerance, the results of this study can be generalized only to middle-aged and older people.…”
Section: Discussionmentioning
confidence: 99%